2017
DOI: 10.1038/s41598-017-05111-8
|View full text |Cite
|
Sign up to set email alerts
|

A connection from stratospheric ozone to El Niño-Southern Oscillation

Abstract: We use reanalysis and observational data to link the lower stratospheric ozone regulation of the ultraviolet radiation (UV-B) component of solar energy to ENSO modulation. Results indicate that during ENSO extremes, the Walker Circulation (WC) and Brewer Dobson Circulation are related to lower stratospheric ozone alterations east of the date line over the Pacific. These in turn are linked to upper tropospheric anomalous dipole temperature patterns on either side of the equator. The ensuing changes in geopotent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
2
16
0
3
Order By: Relevance
“…5) is also consistent with enhanced extratropical planetary waves that propagate into the stratosphere during the warm ENSO phase, resulting in sudden stratospheric warmings and, hence, in enhanced BDC and weaker polar vortices (e.g. Brönnimann et al, 2004;Manzini et al, 2006;Cagnazzo et al, 2009). The very pronounced link between stratospheric O 3 and the ENSO-related dynamical pathways with a time lag of about 3 months is one key finding of the present work.…”
Section: Epf the Vertical Component Of The Planetary Wavesupporting
confidence: 88%
“…5) is also consistent with enhanced extratropical planetary waves that propagate into the stratosphere during the warm ENSO phase, resulting in sudden stratospheric warmings and, hence, in enhanced BDC and weaker polar vortices (e.g. Brönnimann et al, 2004;Manzini et al, 2006;Cagnazzo et al, 2009). The very pronounced link between stratospheric O 3 and the ENSO-related dynamical pathways with a time lag of about 3 months is one key finding of the present work.…”
Section: Epf the Vertical Component Of The Planetary Wavesupporting
confidence: 88%
“…It suggests that March ASO is linked to April P NWUS variations with a lead time of 1 month. This delayed effect can be explained by the process involved in ASO circulation effects; i.e., stratospheric circulation anomalies caused by ASO need a month to propagate to the troposphere in the Northern Hemisphere middle latitudes (Smith and Polvani, 2014;Calvo et al, 2015;Xie et al, 2016;Ivy et al, 2017). Results from the GPCC (Figures 3B,D) agree with those from the GPCP (Figures 3A,C).…”
Section: Root-mean-squared Errorssupporting
confidence: 55%
“…They found that circulation anomalies associated with March ASO variations can propagate to the northwestern United States, leading to local circulation and water-vapor flux anomalies that can affect April P NWUS . This motivates us to investigate whether the March ASO, which has a leading influence on the surface climate in the Northern Hemisphere (Smith and Polvani, 2014;Calvo et al, 2015;Xie et al, 2016Xie et al, , 2017aXie et al, ,b, 2018Ivy et al, 2017;Ma et al, 2019), can be used along with other factors as a predictor of April P NWUS in a statistical model. Results from this new statistical model will be compared with those of the CFS to assess improvements in the predictability of April P NWUS .…”
Section: Introductionmentioning
confidence: 99%
“…In order to detect abrupt changes/shifts, we adopted a manually performed cumulative sum (CUSUM) technique (Wetherill and Brown, 1991), as it performs robustly and is relatively easy to execute (Breaker, 2007;Manatsa and Mukwada, 2017). The analysis of cumulative variables where the cumulative sum of a variable has to be preferred to the variable itself as a measure of performance in climate research has recently gained credibility (Heim et al, 2017;Partanen et al, 2017;Graf and Tomczyk, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…This emanates from the realization that certain climate driven variables do not only respond instantaneously but also to the accumulated effects over the period of time (Manatsa et al, 2015). In this regard, the CUSUM method enables the shift process to be considered holistically, being composed of sequenced and linked events rather than monthly events that are independent (Manatsa and Mukwada, 2017). We also used the Sequential Regime Shift Detector (SRSD, Rodionov and Overland, 2005) in order to confirm the derived shifts and ascertain their p-values.…”
Section: Methodsmentioning
confidence: 99%